Customer Satisfaction Model for Mobile Phone Service Providers in Malaysia - Mohd Jamil, Jastini; Mohd Nawawi, Mohd Kamal; Ramli, Razamin (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
This paper presents the investigation on the effect of image, customer expectation, perceived quality and perceived value on customer satisfaction of mobile phone providers in Malaysia. Then, exploration on the effect of image and customer satisfaction on customer loyalty is also described. Data is gathered through online questionnaire distributed to international students in a selected public university in Malaysia. Partial Least Squares Structural Equation Modeling (PLS-SEM) has been used to analyze the data. The results found that image and perceived quality have significant impact on customer satisfaction with the regression coefficient values of 0.398 and 0.382 respectively. Image and customer satisfaction were also found to have significantly related to customer loyalty with the regression coefficient values of 0.378 and 0.409 respectively. On the other hand, there is no significant impact found between customer expectation and customer satisfaction, perceived value with customer satisfaction, and customer expectation with perceived value.